Auditoría financiera aplicada en la cooperativa de ahorro y crédito “Sac Pelileo”. Ltda del cantón Pelileo de la provincia de Tungurahua por el período económico comprendido desde el 01 de enero al 31 de diciembre del 2009 - Carrera Almachi, Amada Elizabeth (2011)
A Financial Audit is currently the most important practice because of its great importance in the making of decisions on real audited data, also allowing obtaining an outside opinion on the reasonableness of economic data in a competitive market such as that of the cooperatives, determining their real condition thereof. That is why in the Savings and Credit Cooperative "SAC PELILEO." LTDA, a financial audit has been conducted (to specific accounts) but the basic financial statements have not been fully covered (general balance and result state), so, it has not been possible to determine the reasonableness and accuracy of the information relating to both the accounting treatment and the internal control of the cooperative. As a result, the object of the research study was the Administrative Management - Finance, and the general objective was the application of a financial audit to verify the reasonableness of the financial statements of it. The Financial Audit applied to the Savings and Credit Cooperative "SAC PELILEO." LTDA allowed us to know the real balances of the analyzed accounts and also some difficulties such as financial trawls and erroneous balances, accounts miscalculation, wrong location of assets and improper use of percentages, as well as several weaknesses in the internal control system. This financial audit has contributed to the cooperative through the results, conclusions and recommendations makes decisions that contribute to the improvement of the internal control, accounting management and registration of the economic facts of the entity, that is to say in benefit of the development of the economic -financial situation of the cooperative.